Perilaku Phubbing pada Remaja : Studi Literatur - Nabila Nabila; Aliyyah Dhiyah Ulhaq; Risma Anita Puriani; Rizki Novirson (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Phubbing behavior has become a significant global phenomenon among adolescents, with multidimensional impacts on social interactions, mental health, and academic performance. This article aims to analyze the causal factors, impacts, and prevention strategies of phubbing. This research uses a literature study type by analyzing several relevant articles. The results showed that the main factors driving phubbing include smartphone addiction, Fear of Missing Out (FoMO), boredom, and low self-control. Impacts include decreased quality of social interactions, increased anxiety, decreased academic focus, and physical impairments such as headaches. Although some studies indicate phubbing does not significantly affect friendship satisfaction in certain groups, the phenomenon generally disrupts interpersonal relationships. The proposed solution involves a holistic approach through digital literacy education, family interventions, school policies and physical activity.